Regional Integration and Institutional Capacities: an Exploratory Analysis of their Impact on Development in Central America and the Dominican Republic - Prestol, Joaquín (Revista del CLAD Reforma y Democracia, 2022)
Central American integration is a process that has brought benefits to its members in various areas. An expected product of this process is the strengthening of the institutional capacities of its participants and their consequent economic and institutional development. However, although the members of the Central American Integration System, especially Costa Rica, have shown progress in different areas of the concept of institutional capacities, the evidence points to divergences. Based on the operationalization of the concept of institutional capabilities -with some indicators of interest and secondary sources of information-, this paper argues that a possible process of clustering of institutional development and, therefore, of human development in the region has been avoided, differentiating between the countries of the Northern Triangle, those that do not belong to this zone and those that are outside the Isthmus. As a consequence, the importance of integration as a provider of anchors for institutional development and how the process in Central America can help member countries to improve their institutional capacities and their prospects for human development is discussed.
Keywords: Evaluation; Evaluation Models; Policies Evaluation; Programs Evaluation; Methods; Decisions Making; Colombia